Optic Nerve Gliomas - Wladis, Edward J.; Adamo, Matthew A.; Weintraub, Lauren (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objectives To describe the diagnostic and management features of optic nerve gliomas.Design Literature review.Results Optic nerve gliomas are generally benign in the pediatric age group although they are usually malignant and aggressive in adults. As such, the mechanisms by which these lesions are diagnosed, the systemic implications, the goals of intervention, and the nature of therapeutic management all differ between these tumors.Conclusions This article addresses these lesions and discusses the diagnostic and therapeutic paradigms by which they may be approached.
Keywords: glioma; optic nerve glioma; malignant optic nerve glioma